2017
DOI: 10.4067/s0370-41062017000500002
|View full text |Cite
|
Sign up to set email alerts
|

Depresión posparto en padres: ¿por qué también es importante?

Abstract: ResumenLa supervisión de salud es una oportunidad privilegiada para acompañar a las nuevas familias en su transición a la parentalidad. Este período trae importantes desafíos para la madre y el padre, y en ocasiones la demanda puede superar los recursos emocionales de la familia; este desbalance puede favorecer que madres y padres presenten sintomatología depresiva. La depresión posparto puede afectar de uno a dos de cada diez hombres, siendo la depresión materna un factor de riesgo importante para desarrollar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Depressed fathers, more than depressed mothers, tend to be more avoidant and carry out activities that affect their parenting, such as increasing their workload (Bruno et al, 2020). The scarce Chilean studies on this subject recommend including screening for paternal postpartum depression in health check-ups (Pérez & Brahm, 2017). This initiative could help identify possible barriers for paternal involvement and promote greater parental co-responsibility from the birth of the child.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depressed fathers, more than depressed mothers, tend to be more avoidant and carry out activities that affect their parenting, such as increasing their workload (Bruno et al, 2020). The scarce Chilean studies on this subject recommend including screening for paternal postpartum depression in health check-ups (Pérez & Brahm, 2017). This initiative could help identify possible barriers for paternal involvement and promote greater parental co-responsibility from the birth of the child.…”
Section: Discussionmentioning
confidence: 99%
“…Padres, más que madres deprimidas, tienden a ser más evitativos y a desarrollar actividades que los mantengan al margen de la crianza, como aumentar la carga de trabajo (Bruno et al, 2020). Los escasos estudios en torno a esta materia en Chile recomiendan incluir el tamizaje de depresión posparto masculina en los controles de salud (Pérez & Brahm, 2017). Esta sería una gran iniciativa que ayudaría a pesquisar posibles barreras del involucramiento paterno y promover mayor corresponsabilidad desde el nacimiento del hijo/a.…”
Section: Discussionunclassified
“…powerful (by means of medically) screening test and some specific. 2) Health self-care system issues related to depression such as potential harm, policies for referral and cost effectiveness [4].…”
Section: Epidemiologymentioning
confidence: 99%
“…Paternal PPD refers to a new father who suffers from depressive symptoms within a 12 month perinatal period after the birth of an infant [ 5 , 6 ]. Paternal PPD has a negative impact on family members, the impact can reduce early parent-infant interactions resulting in poor communication and stimulation [ 7 ].It can also have further long-term adverse impacts on an infant’s physical growth and their cognitive, behavioral, and social development [ 8 , 9 ]. Previous research has shown the rate of paternal PPD ranges from 5.4–13.6%, depending on sample size, measurement scales, and different population characteristics [ 4 , 10 12 ].…”
Section: Introductionmentioning
confidence: 99%